Rancang Bangun Media Pembelajaran Interaktif pada Mata Pelajaran Desain Grafis - Fahmi Romisa; Dewi Rosita (CV. ALIM'SPUBLISHING, 2024)
. Design and Development of Interactive Learning Media in Graphic Design Subjects is a research that aims to develop effective and practical interactive learning media on basic graphic design topics. This research uses the ADDIE development model, which consists of five development stages: analysis, design, development, implementation, and evaluation.At the analysis stage, this research understands the problems found in the use of learning media in graphic design subjects, such as the limited use of print media and the need for more interactive and interesting media. At the design stage, this research develops a learning media design that involves multimedia elements such as text, images, graphics, sound, video, animation and comprehensive simulations. At the development stage, this research develops multimedia-based interactive learning media, which can provide certain forms of interaction that allow users to interact actively with the program. The research results show that the Basic Graphic Design interactive learning media developed is valid from the instructional and display aspects, and is practical and suitable for use for basic graphic design learning. Thus, this research contributes to the development of interactive learning media that is effective and practical in improving the quality of learning in graphic design subjects.